Portāla Santa.lv auditorijas vajadzības, lietošanas paradumi un satura konverģences analīze - Lūse, Lelde (Latvijas Universitāte, 2021)
Bakalaura darba “Portāla Santa.lv auditorijas vajadzības, lietošanas paradumi un satura konverģences analīze” mērķis ir noskaidrot, portāla “Santa.lv” lasītāju lietošanas paradumus, vajadzības un to apmierinājumu, kā arī izpētīt satura konverģenci starp izdevniecības “Žurnāls Santa” drukātajiem medijiem un portālu. Darba teorētiskajā daļā tika apkopota akadēmiskā literatūra par mediju konverģenci, mediju auditoriju, auditorijas iedalījumu un raksturojumu, mediju lietojuma un apmierinātības teoriju, kā arī paredzamās vērtības teoriju. Bakalaura darba pētījumā izmantota kontentanalīze portāla satura un satura konverģences izpētei, anketa portāla auditorijas vajadzību un lietošanas paradumu tendenču noteikšanai, un daļēji strukturēta intervija ar portāla “Santa.lv” galveno redaktoru. Noskaidrots, ka portālā “Santa.lv” novērojama satura konverģence, taču portāla piedāvātais saturs ir plašs un visaptverošs. Auditorijas vēlmes no portāla puses tiek ņemtas vērā, tādēļ nereti arī auditorija iesaistās portāla satura veidošanā.

The aim of the bachelor's thesis “Portal Santa.lv audience needs, usage habits and content convergence analysis” is to find out the usage habits, needs and satisfaction of the readers of the portal “Santa.lv”, as well as to study the convergence of content between the publishing house’s “Žurnāls Santa” printed media and the portal. In the theoretical part of the thesis was summarized the academic literature on media convergence, media audience, audience division and characterization, media use and satisfaction theory, as well as the theory of expected value. In the research of the bachelor's thesis was used content analysis to study the content and convergence of the content of the portal, a questionnaire to determine the needs and usage trends of the portal audience, and a partially structured interview with the editor-in-chief of the portal "Santa.lv". It has been found out that there is a great convergence of content on the portal “Santa.lv”, however the content offered by the portal is wide and comprehensive. The wishes of the audience on the part of the portal are taken into account, therefore often the audience is also involved in the creation of the content of the portal. In the theoretical part of the thesis was summarized the academic literature on media convergence, media audience, audience division and characterization, media use and satisfaction theory, as well as the theory of expected value. In the research of the bachelor's thesis was used content analysis to study the content and convergence of the content of the portal, a questionnaire to determine the needs and usage trends of the portal audience, and a partially structured interview with the editor-in-chief of the portal "Santa.lv". It has been found out that there is a great convergence of content on the portal “Santa.lv”, however the content offered by the portal is wide and comprehensive. The wishes of the audience on the part of the portal are taken into account, therefore often the audience is also involved in the creation of the content of the portal.
Portal Santa.lv audience needs, usage habits and content convergence analysis
Keywords: Komunikācijas zinātne; Mediju konverģence; konverģence; auditorija; Santa.lv; Satura konverģence